How Water Scarcity Will Shape World Power: A Case Study of Ethiopia’s Grand Ethiopian Renaissance Dam - Stiplosek, Katherine I. (Tufts Archival Research Center, 2022)
In 2018, The National Security Journal, published by Harvard Law School, described water scarcity as the most understated global security risk. Water Scarcity touches every continent on the planet. UNICEF reports that four billion people – nearly two thirds of the world’s population – experience severe water scarcity for at least one month each year. As early as 2025, half of the world’s population could be living in areas facing water scarcity. In light of the water scarcity crisis, water - an essential resource - will become increasingly important. What happens when a country dams a major water resource to collect - and profit off of – this commodity? Through case study and analysis of Ethiopia’s Grand Ethiopian Renaissance Dam, this thesis seeks to examine how a country’s autonomous access to a water resource will affect its power, using the water scarcity crisis as a backdrop for all analysis and conclusions. I conduct an examination of the three major countries affected by the dam, Egypt, Ethiopia, and Sudan, including their environmental factors, population requirements, and geopolitical histories. I also examine how the GERD’s construction progress and negotiations have evolved. I find that Ethiopia’s construction of the GERD will increase its world power threefold. First, the country’s autonomous access to water resources will endow it with a substantial supply of a scarce but necessary resource, allowing the country to sustain its growing population and satisfy concerns over food security. Furthermore, this access will allow Ethiopia to maintain control over security and control over production in the global sphere. As the water scarcity crisis becomes more prominent across our planet, my thesis hopes to provide insight on the effects of this unravelling phenomena.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the International Relations Program.